Eviota rubriceps, a new goby from the Southwestern Pacific Ocean, with comments on E. mikiae and E. raja (Teleostei: Gobiidae) - Greenfield, David W.; Jewett, Susan L. (Zootaxa, 2011)
A new species of goby, Eviota rubriceps, most similar to E. nigrispina, is described from Indonesia, Papua New Guinea, and the Philippine Islands. Both species have the lower two thirds of the body dark in preserved specimens, belong to the cephalic sensory-pore pattern group 2 of Lachner and Karnella (1980), have an 8/7 dorsal/anal formula, and unbranched pectoral-fin rays. Eviota rubriceps differs from E. nigrispina in live and preserved coloration and in caudal-peduncle depth. The descriptions of E. mikiae and E. raja are expanded based on additional materials.